2021
DOI: 10.1021/acsomega.1c02618
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Comprehensive Performance Test of Superhydrophobic Paper Mulch Films

Abstract: Paper mulch was treated with nano-zinc oxide and nano-silica dispersion by a brushing method, and its mechanical stability, hydrophobicity, impermeability, and wet strength were verified. The experiment shows that the mulch film after brushing has superhydrophobic properties, and it can also have better superhydrophobic properties and stability after being allowed to stand at room temperature for 240 h and drying under a vacuum of 0.03 MPa under negative pressure. The wet strength test after soaking for differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The ZnO/SiO 2 nanocomposites are beginning to be applied later in the amphiphobic field. The results showed that the composite coating has excellent chemical stability and hydrophobic properties, and the preparation method is simple and effective. All of these studies have a positive guiding significance for the progress of this experiment.…”
Section: Introductionmentioning
confidence: 79%
“…The ZnO/SiO 2 nanocomposites are beginning to be applied later in the amphiphobic field. The results showed that the composite coating has excellent chemical stability and hydrophobic properties, and the preparation method is simple and effective. All of these studies have a positive guiding significance for the progress of this experiment.…”
Section: Introductionmentioning
confidence: 79%
“…Cellulose is the main component of the plant cell wall that can be obtained from wood, cotton, and other plants. Natural cellulose is highly crystalline due to its strong intermolecular hydrogen bonds originating from the hydroxyl groups in cellulose glucose units. , Li et al conducted a study where they prepared a paper-based mulch with exceptional performance . They achieved this by applying a brush-coating technique using dispersions of zinc oxide nanoparticles and silica nanoparticles on a fiber paper floor mulch, as shown in Figure a.…”
Section: Agriculture Mulch From Degradable and Renewable Resourcesmentioning
confidence: 99%
“…(a) Schematic diagram of hydrophobic coated paper-based mulch preparation. Reprinted or adapted with permission under a Creative Commons (CC BY-NC-ND 4.0) from Figure 1 in ref . Copyright 2021, American Chemical Society.…”
Section: Agriculture Mulch From Degradable and Renewable Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Superhydrophobic surface refers to the surface where the contact angle between water droplets and solid materials is greater than 150°, and the rolling angle is less than 10° when solid materials are in contact with water droplets. Superhydrophobic surfaces are widely used in industry, military, and daily life because of their excellent hydrophobicity. An important application of superhydrophobic surfaces is self-cleaning, which can effectively improve the waterproof and antifouling ability of its surface when it is used on glass, clothing, and metal. Superhydrophobic materials can also be used in pipeline antiscaling, oil–water separation, drag reduction, antiskid, anticorrosion, and other applications.…”
Section: Introductionmentioning
confidence: 99%